Testosterone Increases Circulating Dehydroepiandrosterone Sulfate Levels in the Male Rhesus Macaque - Sorwell, Krystina G.; Kohama, Steven G.; Urbanski, Henryk F. (Frontiers in Endocrinology, 2014)
The adrenal steroid dehydroepiandrosterone (DHEA) and its sulfate (DHEAS) are two of the most abundant hormones in the human circulation. Furthermore, they are released in a circadian pattern and show a marked age-associated decline. Adult levels of DHEA and DHEAS are significantly higher in males than in females, but the reason for this sexual dimorphism is unclear. In the present study, we administered supplementary androgens (DHEA, testosterone and 5α-dihydrotestosterone [DHT]) to aged male rhesus macaques (Macaca mulatta). While this paradigm increased circulating DHEAS immediately after DHEA administration, an increase was also observed following either testosterone or DHT administration, resulting in hormonal profile resembling levels observed in young males in terms of both amplitude and circadian pattern. This stimulatory effect was limited to DHEAS, as an increase in circulating cortisol was not observed. Taken together, these data demonstrate an influence of the hypothalamo-pituitary-testicular axis on adrenal function in males, possibly by sensitizing the zona reticularis to the stimulating action of adrenocorticopic hormone. This represents a plausible mechanism to explain sex differences in circulating DHEA and DHEAS levels, and may have important implications in the development of hormone therapies designed for elderly men and women.